Ethnic Identity and Personality’s Subjective Perception of Time (on Example of Armenian Youth) - A.S. Berberyan; H.S. Berberyan; S.R. Gevorgyan (Культурно-историческая психология)
This work is aimed at studying the characteristics of ethnic identity and subjective perception of time. In the article, identity is considered within the framework of the problem of "Self" and "Self-Image", which implies the presence of information about oneself and the continuity of mental activity as a set of ideas of the individual about himself. The authors focus on the existential and phenomenological approach to the experience of the personality of the concept of time and its connection with ethnic identity. The goal of the study is the investigation of the features of identity and the subjective assessment of the time of the personality in a psychological perspective. The results of an empirical study (N=89) conducted on students of various areas of professional training and courses of study aged 18 to 24 years (M=19,60; SD=1,30) are described. The study was conducted using the author's questionnaire to identify social and demographic data, the questionnaire "Types of ethnic identity of a personality" (G.U. Soldatova, S.V. Ryzhova), the Semantic time differential (L.I. Wasserman and others), Assessment of the severity of ethnic identity and the Scale for express evaluation of feelings associated with ethnicity (N.M. Lebedeva). The obtained results allowed us to identify the main characteristics of ethnic identity and highlight the dominant types among the Armenian student youth. Based on the results of hypotheses testing, statistically significant relationships were revealed between feelings towards one’s nationality and the length of staying in Armenia, between the feeling of being Armenian and the assessment of the past and future.